The Aerodynamic wind Loads of a Naval Surface Combatant in Model Scale - Sari, Sarih; Dogrul, Ali; Bayraktar, Seyfettin (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
Design of the ships considering hydrodynamic and aerodynamic requirements is important especially for naval surface combatants. From the aerodynamic point of view, the superstructure and the flight deck, which is used for landing and take-off operations of aerial vehicles, have to be designed in terms of ship airwake and wind loads. The superstructure combined with the sea and weather conditions has a crucial effect on the flow characteristics such as the turbulence and vortices on the flight deck. This study covers the numerical investigation of aerodynamics of a naval surface combatant designed by the Office of Naval Research (ONR). As a more realistic ship, ONR Tumblehome hull was chosen instead of the generic frigate model SFS2 and ONRT model has been widely used for validation studies as a benchmark geometry. Numerical analyses were conducted by employing the k-. turbulence model and solving the unsteady RANS equations. In the present study, the axial and tangential velocity distributions on the flight deck of ONRT were firstly validated in model scale. Following this, one more model scale geometry was generated and the aerodynamics of these vessels were investigated in headwind conditions. Thus, the scale effects on the aerodynamics of the ship were observedmaintaining the dynamic similarity based on Reynolds number. Furthermore, the aerodynamic wind loads on the ONRT surface combatant vessel are presented for various wind-over-deck (WOD) angles in one model scale.
Keywords: Aerodynamics; CFD; ONRT; RANS; Ship airwake; Computer Science; Engineering